Just a Teacher's Pet - Mayer, Mercer 1943- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2015)
"Little Critter is not too happy when a new student gets special treatment. But when the teacher's pet shows that she's a team player, Little Critter and his classmates discover that they've made a great new friend"--Amazon.com.
Keywords: Little Critter (Fictitious character) -- Juvenile fiction; Kindness -- Juvenile fiction; Friendship in children -- Juvenile fiction; Little Critter (Fictitious character) -- Fiction; Kindness -- Fiction; Friendship -- Fiction